2017
DOI: 10.17979/reipe.2017.0.09.2451
|View full text |Cite
|
Sign up to set email alerts
|

Theraphy 2.0: Chegar mais perto dos que estão longe

Abstract: ResumoEste estudo tem como objetivo explorar a utilização das Tecnologias da Informação e da Comunicação (TIC) nos processos terapêuticos e de aconselhamento. AbstractThis study aims to explore the use of Information and Communication Technologies (ICTs) in the therapeutic and counselling processes. Two hundred and fifty-one professionals from 7 different countries, who underwent therapy or counselling, answered an on-line questionnaire. The results revealed that 52.97% of those who already used an on-line to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 3 publications
4
8
0
Order By: Relevance
“…A study in other countries revealed that, among those who have employed any online means of practicing counseling and therapy, 52.97% had a positive or very positive opinion about the use of these tools. In this study, e-mail was the most widely used online tool, and the computer and smart phone were the most frequently used equipment [14]. Different circumstances and factors seem to contribute to explain the different attitudes and the adoption (or not) of this type of resources [23].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…A study in other countries revealed that, among those who have employed any online means of practicing counseling and therapy, 52.97% had a positive or very positive opinion about the use of these tools. In this study, e-mail was the most widely used online tool, and the computer and smart phone were the most frequently used equipment [14]. Different circumstances and factors seem to contribute to explain the different attitudes and the adoption (or not) of this type of resources [23].…”
Section: Introductionmentioning
confidence: 84%
“…The questionnaire included 30 questions divided into three sections: (i) socio-demographic data, with 9 questions; (ii) experience before the COVID-19 pandemic, with 7 questions; and (iii) current experience using ICTs in psychology sessions (namely web-based interventions during the lockdown period), with 14 questions. The questions were designed based on a previous questionnaire developed for the purpose of studying the use of ICTs in the provision of therapy and counseling [14], as well as on the advantages and challenges identified in the literature about the use of these technologies on psychological counseling.…”
Section: Instrumentsmentioning
confidence: 99%
See 3 more Smart Citations